The use of Triamcinolone Injection in treatment of refractory benign Esophageal Stricture in children - Yassin Osman, Ahmed Zuhry; Ahmed, Faisal Alkhateeb; ahmed sayed, Zain El-Abdeen; Badawy Ali, Ahlam; Abdel-Wahab Mohamed, Hossam Mahmoud; Ibrahim Abu Faddan, Nagla Hassan (Journal of Neonatal Surgery, 2025)
Objectives: To evaluate the efficacy of Intra-lesional triamcinolone injection in the management of refractory benign esophageal Stricture in children. Methods: Before endoscopic dilatation, triamcinolone acetate (40 mg/ml) was be applied in the first 5 dilations with an interval of one week between the first and second dilation and then every 2 weeks. Results: A total of 67 children with refractory benign esophageal stricture out of 183 children (36.6%) who presented with esophageal stricture were enrolled in the study, Cause of esophageal stricture was post-corrosive injury (n=59, 88.1%), with a smaller proportion attributed to post-TEF repair (n=8, 11.9%), There was a significant reduction in the number of dilatations required before and after the triamcinolone injections. The mean maximum dilation improved from 10.66 mm SG(Savary-Gilliard) before injections to 13.13 mm SG after injections, periodic dilatation index (PDI) showed significant reduction post-treatment. The mean PDI decreased from 1.07 to 0.27, There was a significant improvement in the grades of dysphagia, there was no significant changes in cortisone levels, ACTH (Adrenocorticotropic hormone) levels showed no significant change, there were no major complications of the procedure. Conclusion: findings suggest that intralesional triamcinolone injection is an effective and safe treatment option for refractory benign esophageal strictures in children.